Analisis Kinerja Pegawai pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Karawang - Septiana Krisdayanti Marpaung; Suroso Suroso; Flora Patricia Anggela (Universitas Batanghari, 2022)
This research aims to find out the performance assessment system, as well as related factors in improving the performance of employees in the Community Empowerment Office and Karawang Regency Village. This study uses descriptive methods with data collection techniques in the form of interviews and observations. The results of this study are in conducting data on employee performance, the Community Empowerment Office and Karawang Regency Village using a system called PARE (Performance Agreetment Report by Electronic). As for improving performance, a leader with employees must have a good communication relationship, so that it can increase employee motivation and morale, and can foster work discipline.